Homero Árcade: uma análise da tradução da Marquesa de Alorna para o Canto I da Ilíada - Cerdas, Emerson [UNESP]; Borges, Joana Junqueira [UNESP] (My University, 2017)
In the Arcadian period, the practice of translation has been promoted, particularly of the Greek and Latin classics, which were regarded as the main source for ideals of truth, nature, reason, clarity and whose poetry was considered to properly combine utility and delight. A prominent representative of this period was the Marquise of Alorna who, among other works, has translated Book 1 of Homer's Iliad. We will therefore seek to analyse the features of the translation carried out by the Marquise, drawing on the reflections on translation prevalent in her day.
Arcadian Homer: An analysis of the Marquise of Alorna's translation of Book 1 of the Iliad
Keywords: Homer; Marquise of alorna; Tradition; Translation